Breast conserving therapy in breast cancer - Niwińska, Anna; Nagadowska, Monika (Contemporary Oncology/Współczesna Onkologia, 2002)
The use of breast conserving therapy (BCT) rather than modified radical mastectomy (MRM) for the treatment of breast carcinoma is nowadays an option for the majority of women with early stage breast cancer. Clinical trials established the value of breast-conserving treatment including the macroscopic removal of the tumor followed by local radiation therapy (RT) for stage I and II invasive carcinomas. The authors presented the current knowledge about breast conserving treatment in patients with breast cancer. The indications and contraindications for this type of treatment were presented. There are absolute contraindications like multicentric disease within the breast, a history of previous therapeutic irradiation to the breast region, pregnancy or persistent positive margins after reasonable surgical attempts. The most common relative contraindications like a history of collagen vascular disease, multifocal disease, tumor size in relation to the breast size are also discussed. Authors also pointed out that certain clinical and pathologic features should not prevent patients from being candidates for BCT for example : the presence of clinical or pathologic involvement in axillary lymph nodes, or family history of breast cancer as little is known about the increased risk of failure. The surgical and radiotherapy techniques were discussed. Possible complications of RT include arm edema, brachial plexopathy, decreased arm mobility, soft-tissue necrosis, rib fractures, radiation pneumonitis and radiation related heart disease. However, the risk of various complications is strongly dependent on technique, including dose and fractionation. Special attention was paid to the complication and local recurrence rate. Risk factors for local and distant recurrence after BCT were discussed. The goal of BCT is to minimize the risk of local recurrence while leaving the patient with a cosmetically acceptable breast. The assessment of cosmetic effects is equally important to the oncological effects when using this type of surgery. The authors also addressed the psychological issues, factors influencing patients' and physicians' decision making and the cost-effectiveness of breast conserving therapy in the early stages of breast cancer. The authors presented the state of the art in breast cancer treatment bearing in mind that determining the optimal care of breast therapy for each patients cannot be reduced to an algorithm.